An Oxofluoride Catalyst Comprised of Transition Metals and a Metalloid for Application in Water Oxidation. Issue 37 (20th July 2015) - Svengren, Henrik; Hu, Shichao; Athanassiadis, Ioannis; Laine, Tanja M.; Johnsson, Mats
Abstract The application of the recently discovered oxofluoride solid solution (CoxNi1−x)3Sb4O6F6 as a catalyst for water oxidation is demonstrated. The phase exhibits a cubic arrangement of the active metal that forms oxo bridges to the metalloid with possible catalytic participation. The Co3Sb4O6F6 compound proved to be capable of catalyzing 2H2O→O2+4H++4e− at 0.33 V electrochemical and ≤0.39 V chemical overpotential with a TOF of 4.4⋅10−3, whereas Ni3Sb4O6F6 needs a higher overpotential. Relatively large crystal cubes (0.3–0.5 mm) are easily synthesized and readily handled as they demonstrate both chemical resistance to wear after repeated in situ tests under experimental conditions, and have a mechanical hardness of 270 V0.1 using Vickers indentation. The combined properties of this compound offer a potential technical advantage for incorporation to a catalytic interface in future sustainable fuel production.